PREFERENCES FOR PROCEDURES AND LEARNING MEDIA DEVELOPMENT MODELS - Nuha, Muhammad Ullin; Krisgiantoro, Nofan Gierdo; Syafiq, M. Audi Aenu; Ferdiansyah, Arif Kurnia (Proceeding of International Conference of Islamic Education, 2024)
Learning media as a component of the learning system must be in accordance with the learning components so that its function is optimal in facilitating learning activities. This article aims to explain the selection criteria and procedures for developing adaptive learning media. This article is the result of a literature review by searching various references to obtain valid and reliable data. The results of this research show that in general the learning media development procedure consists of three main steps, namely: 1) planning, 2) design, 3) development, and 4) evaluation. The learning media development models are as follows: ADDIE, ASSURE, 4D, PIE, Roblyer, Hannafi & Peck, Dick & Carey, and Smith & Ragan. Of course, each development model will be implemented according to learning needs in order to achieve learning goals.